Sosialisasi Prosedur Pelaksanaan Layanan Bimbingan Kelompok Teknik Self-Control untuk Mengurangi Loneliness Siswa Pada Musyawarah Guru BK SMP Kota Palu - Lestari, Mardi; Ratu, Bau; Syahran, Ridwan; Arifyadi, Azam; Felayati Silalahi, Micha; Fitriani, Dian (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The implementation of guidance services for students at junior high schools under the auspices of MGBK Palu has been observed to be suboptimal, with the forms of service and innovation implemented by guidance counsellors proving ineffective. The main problems with the service partners include: the optimisation of processes and innovations in guidance services for students is not yet optimal; guidance counsellors at junior high schools under the auspices of MGBK Palu are not yet fully aware of the procedures for implementing self-control group guidance in overcoming loneliness. This service aims to provide guidance counsellors with the understanding, skills and abilities to carry out their services at school. The participants of this community service activity were 20 junior high school guidance counsellors who are members of the Palu City Junior High School MGBK. The core activities were carried out over 1 day of socialisation and 3 months of mentoring. The stages of implementation of this community service were through socialisation and mentoring. The results of community service showed that the level of competence of teachers at the community service partner location increased in the implementation of guidance services. The implications of community service were seen in the implementation of socialisation, the utilisation of services by guidance counsellors, innovations in implementing guidance counselling services, and the evaluation of activities after the implementation of community service by partners.